C-reactive protein in antiphospholipid syndrome: relationship with cardiovascular pathology - N V Seredavkina; T M Reshetnyak; E N Alexandrova; A A Novikov; E S Mach; T V Popkova (Научно-практическая ревматология)
Objective. To assess relationship of high sensitivity C reactive protein (hsCRP) level in pts with antiphospholipid syndrome (APS) with clinico-laboratory features and cardiovascular pathology. Material and methods. 206 pts were included. 58 from them had primary APS (PAPS), 72 –systemic lupus erythematosus (SLE) with APS and 76 – SLE. 29 from 76 pts of the latter group were positive on anticardiolipin antibodies (ACA) – SLE with antiphospholipid antibodies (APhL) and 47 – low positive or negative on ACA – SLE without APhL. 72 persons without autoimmune diseases were included into control group. CRP (with high sensitivity immuno-nephelometric assay), APhL (with solid phase immuno-enzyme assay), plasma lipids were evaluated, sonography with measurement of intima-media complex (IMC) thickness of common carotid arteries, carotid artery bulbs and internal carotid arteries, electrocardiography (ECG), echocardiography (EchoCG), Holter ECG monitoring were performed. Results. HsCRP serum level in pts was significantly higher than in control: 2,55 [0,71; 7,04] mg/l (varied from 0,15 to 39,85) vs 0,68 [0,26; 1,97] mg/l (varied from 0,1 to 9,61), p<0,001. Most high hsCRP concentration was found in SLE with APS (p=0,02). HsCRP level in pts with PAPS with history of combined or isolated arterial thrombosis was significantly higher than in pts with SLE and APS having the same localization of thrombosis. HsCRP concentration less than 3 mg/l correlated with duration of postthrombotic period in pts with PAPS. HsCRP level also correlated with triglyceride concentration, body mass index, summated coronary risk and magistral arteries IMC thickness. Conclusion. HsCRP elevation in pts with APS was associated with development of combined and arterial thrombosis as well as with traditional risk factors of atherosclerosis.